FORMING HALAL TO BRAND? FACTORS AFFECTING CONSUMER'S INTENTION TO BUY HALAL BRANDS - Gugyh Susandy; Reni Dian Octaviani; Rita Komaladewi; Susi Yasmin (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2022)
Around the world, many consumers (e.g. Muslim consumers) look for halal brands. The benefits of halal products affect consumer attitudes and behavior in terms of intention to buy halal products and willingness to pay for halal products (Azizi and Chok, 2013). The purpose of this study is to see the factors that influence consumer intention to buy halal brands. It was carried out by determining the branding instrument (brand image, perceived brand quality, brand satisfaction, brand loyalty, and brand loyalty) on the research questionnaire to explain the purchasing behavior of halal brands. Novelty: Indonesia and Malaysia are countries which are potential for not only halal food market, but also as a producer. However, the opportunity as a producer has not been fully utilized. Research Methods: This research used explanatory survey method, data were collected by means of an online questionnaire from sample of 52 respondents consisting of 47 Indonesian respondents (Bandung, Subang, Jakarta, Cianjur, Semarang, Yogyakarta and Majalengka Regent) and 5 Malaysian respondents (students of KUIS, Selangor) and analyzed using SPSS 22. Finding/Results: The research shows that brand image, brand perceived quality, brand satisfaction, brand trust, and brand loyalty have positive effect on brand purchase intention.